2020
DOI: 10.1016/j.gca.2020.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Sr in coccoliths of Scyphosphaera apsteinii: Partitioning behavior and role in coccolith morphogenesis

Abstract: Coccolithophores are important contributors to global calcium carbonate through their species-specific production of calcite coccoliths. Nannofossil coccolith calcite remains an important tool for paleoreconstructions through geochemical analysis of isotopic and trace element incorporation including Sr, which is a potential indicator of past surface ocean temperature and productivity. Scyphosphaera apsteinii (Zygodiscales) exhibits an unusually high Sr/Ca ratio and correspondingly high partitioning coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…The latter, together with the Braarudosphaeraceae, do not calcify in the haploid phase but produce coccoliths with high-Mg calcite [54] during the diploid phase, suggesting different cellular ion transport pathways or rates of ion uptake compared to other coccolithophores. In a similar vein, strontium is an interesting element that has been demonstrated to have relatively low concentrations in the coccoliths of most taxa, except for one striking example, the Pontosphaeraceae [130,131] and an extinct Jurassic morphospecies [132]. A silicon dependency in the heterococcolith formation appears to be correlated with the status of "obligate calcifier" [75], whereas those that lack the same can survive without calcifying (Figure 8).…”
Section: Functional Morphology: Exploring the Traitscape Of Coccolith...mentioning
confidence: 84%
“…The latter, together with the Braarudosphaeraceae, do not calcify in the haploid phase but produce coccoliths with high-Mg calcite [54] during the diploid phase, suggesting different cellular ion transport pathways or rates of ion uptake compared to other coccolithophores. In a similar vein, strontium is an interesting element that has been demonstrated to have relatively low concentrations in the coccoliths of most taxa, except for one striking example, the Pontosphaeraceae [130,131] and an extinct Jurassic morphospecies [132]. A silicon dependency in the heterococcolith formation appears to be correlated with the status of "obligate calcifier" [75], whereas those that lack the same can survive without calcifying (Figure 8).…”
Section: Functional Morphology: Exploring the Traitscape Of Coccolith...mentioning
confidence: 84%
“…The current knowledge on coccolithophore phylogeny and Sr/Ca cannot exclude one or the other solutions, hence a possible ion pump or polysaccharide could have favored the high Sr/Ca in C. crassus. Recently, Meyer et al (2020) observed that Sr 2+ and Ca 2+ fluxes in the coccolith vesicle for coccolithogenesis does not solely govern Sr incorporation in the coccolith speculating than that possible species-specific polysaccharides dedicated to a peculiar coccolith morphology may act in the high Sr/Ca observed in Scyphosphaera.…”
Section: Discussionmentioning
confidence: 99%
“…In order to better understand the mechanism of coccolithogenesis, it is important to obtain information about the presence and distribution of minor elements as well as organic compounds in coccoliths 14 . While the distribution of minor elements in general is helpful, the one of Si is particularly important because Si plays a role in morphogenesis on Si-requiring species, contrary to other minor elements such as Sr 7 . Unfortunately, very little is known about the presence of Si in coccoliths, and even less about its distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the study of coccolithophore calcification physiology has mainly focused on the structural components of coccolith calcite, i.e. calcium ion (Ca 2+ ) and dissolved inorganic carbon 1 , 5 , 6 , and on the fractionation of certain minor elements such as strontium (Sr) 7 9 . Since silicon is not a component of calcite, the Si requirement of some coccolithophore species had not been expected and was not realized until Durak et al 10 showed that some species need Si to calcify.…”
Section: Introductionmentioning
confidence: 99%